Qualitative Review of Monitoring and Evaluation Practices in Higher Institutions in Uganda - Otyola, Roberts Wandera; Bukenya, John; Nalwadda, Proscovia; Kamaga, Edward; Wamani, Godfrey Bagamba; Bantebya, Suzan; Jonathan, Mukisa (European Journal of Human Resource, 2023)
Purpose: The purpose of the study was to investigate how the practices employed in the Monitoring and Evaluation processes contribute to the overall goal of Higher Education Institutions in Uganda. It was carried out using a qualitative document review method. The study was guided by five objectives: to examine the legal framework of monitoring and evaluation in Uganda's higher education institutions, to formulate monitoring and evaluation policy in higher education institutions, to assess the establishment of constituent colleges of Makerere university, to examine how monitoring and evaluation policy affects university teaching quality, and to assess how the M & E policies are performed at the university senates and council committees. Findings: The findings of the study show that the Uganda Ministry of Education and Sports (MoES) has prioritized the concept of quality assurance in the sector at all education levels. Each college at Makerere University is administered as a semi-autonomous entity within the larger university and the overall supervision of the college is the responsibility of the university council and it is the responsibility of College leadership to conduct regular M&E of services offered in their units to ensure that quality is not compromised. Student evaluation of teaching (SET) is used in Makerere university where questionnaires are given to students to evaluate the quality of instruction by their instructors at the end of every lecture, course or semester. There is also peer observation of teaching where colleagues from the same department, subject or discipline help in giving and receiving feedback from one another on the quality of teaching and effectiveness. Recommendations: However, the study recommends that monitoring and evaluation should be implemented even in the secondary and primary education, institutions should have both internal and external evaluations for consistency and transparency, more research should be done on the challenges facing the established policies in higher education institutions of learning in Uganda.